MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN AUDIO VISUAL - Nora Afnita; Dian Puspita Sari; Arif Arafat; Joni Indra Wandi; Febri Wandha Putra (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2022)
The phenomenon that occurs is that students' interest begins to decrease while undergoing learning activities. This was followed by a decrease in motivation in students. This is due to the minimal use of media by teachers. This study aims to determine the effect of audio-visual learning media on students' learning motivation in Islamic Religious Education lessons. This research method is quantitative with a true experiment approach. The population in this study were fifth grade elementary school students, totaling 40 students. The sampling technique by means of total sampling, so that the number of samples in this study amounted to 40 students. The instrument used is a Likert model scale with five alternative answers and a questionnaire about student motivation. The validity test uses the Pearson correlation with a validity value of 0.672. The reliability test uses Cronbach's alpha, with a reliability value of 0.782. The data analysis technique used is the t-test with the help of the SPSS application. The results of the study show that the audio-visual media has a significant and positive effect on students' learning motivation.